Cyberentity and its consistency in the cyber-physical-social-thinking hyperspace. (January 2020) - Dhelim, Sahraoui; Huansheng, Ning; Cui, Shan; Jianhua, Ma; Huang, Runhe; Wang, Kevin I-Kai
Abstract: The Internet of Things (IoT) computing paradigm and its variants, such as the Social Internet of Things (SIoT) and the Internet of People (IoP), have enabled the interconnection of billions of devices with existing computing systems like the social networking platforms. Such interconnection allows IoT applications to offer large-scale context-aware services. On the other hand, the pervasive integration of the IoT and the Cyber-Physical Systems (CPS) have posed many new challenges on the cyber modeling of physical, social and thinking entities. After mapping all the basic elements that form the physical, social and thinking spaces, these elements will be represented in the cyberspace as cyber entities, which are the most elementary particles of the cyberspace. Cybermatics was proposed as a holistic field for the systematic study of cyber entities in the cyberspace and their functions, properties, and conjugations with entities in conventional spaces. In this paper, we emphasize the temporal parts, life cycle and inter-relations of the cyber entities. The potentials of endurance and perdurance cyber mapping are also discussed. Furthermore, a mapping model that incorporates the cyber entity evolution and temporal parts consistency is proposed and presented using a smart home as a use case scenario.